Mesenchymal Stem Cells Reconditioned in Their Own Serum Exhibit Augmented Therapeutic Properties in the Setting of Acute Respiratory Distress Syndrome. (20th June 2019) - Xu, Amy L.; Rodriguez, Luis A.; Walker, Kerfoot P.; Mohammadipoor, Arezoo; Kamucheka, Robin M.; Cancio, Leopoldo C.; Batchinsky, Andriy I.; Antebi, Ben
Abstract: Mesenchymal stem cells (MSCs) are a promising form of therapy for acute respiratory distress syndrome (ARDS). The objective of this study was twofold: (a) to characterize cytokine expression in serum from ARDS subjects receiving MSCs and (b) to determine MSC function following "preconditioning" with ARDS serum. In phase I, serum from three cohorts of animals (uninjured [no ARDS, n = 4], injured untreated [ n = 5], and injured treated with approximately 6 million per kilogram MSCs [ n = 7]) was analyzed for expression of inflammatory mediators. In phase II, the functional properties of bone marrow porcine MSCs were assessed following "preconditioning" with serum from the three cohorts. In phase III, the findings from the previous phases were validated using human bone marrow MSCs (hBM-MSCs) and lipopolysaccharide (LPS). Serum from injured treated animals had significantly lower levels of interferon-γ and significantly higher levels of interleukin (IL)-1 receptor antagonist (IL-1RA) and IL-6. Similarly, upon exposure to the injured treated serum ex vivo, the MSCs secreted higher levels of IL-1RA and IL-10, dampened the secretion of proinflammatory cytokines, exhibited upregulation of toll-like receptor 4 (TLR-4) and vascular endothelial growth factor (VEGF) genes, and triggered a strong immunomodulatory response via prostaglandin E2 (PGE2 ). hBM-MSCs demonstrated a similar augmented therapeutic function following reconditioning in a LPS milieu. Administration of MSCs modulated the inflammatory milieu following ARDS. Exposure to ARDS serum ex vivo paralleled the trends seen in vivo, which appear to be mediated, in part, through TLR-4 and VEGF and PGE2 . Reconditioning MSCs in their own serum potentiates their immunotherapeutic function, a technique that can be used in clinical applications. Stem Cells Translational Medicine 2019;8:1092–1106 : Abstract : In phase I, sera from three cohorts of swine—"uninjured, " "injured untreated" (acute respiratory distress syndrome due to smoke inhalation and burn), and injured treated with mesenchymal stem cells (MSCs)—were analyzed for their cytokine levels (top left). In phase II, the MSCs were "preconditioned" with serum from the three cohorts, and their functional characteristics (bottom) and immunomodulatory function (top right) were evaluated.